The Changes in Extreme Precipitation over Malaysia During Boreal Winter - Noor Amalina Bokri; Ester Salimun (E3S Web of Conferences)
Climate change is altering the Earth’s atmospheric and oceanic conditions, leading to increased frequency and intensity of extreme weather patterns. This study evaluates the ability of three High-Resolution Model Intercomparison Project (HighResMIP) CMIP6 models, CMCC-CM2VHR4, MRI-AGCM3-2-S, and FGOALS-F3-H to simulate extreme precipitation events during boreal winter over Malaysia. Three extreme indices, Consecutive Wet Days (CWD), Simple Precipitation Intensity Index (SDII) and Total Precipitation (PRCPTOT) from the Expert Team on SectorSpecific Climate Indices (ET-SCI) have been utilized for analysis. Future projections of extreme rainfall are based on the most accurate model identified from this evaluation. Statistical methods including the Taylor diagram and significance test are employed in the analysis. Results indicate that the MRI-AGCM3-2-S model exhibits superior capability in simulating all three extreme indices over the study region. This information provides valuable insights for local authorities to strategise their mitigation and adaptation plans at the local scale.